PAREMIOLOGICAL UNITS REPRESENTING TIME IN ENGLISH - Boltaqulova Gulnoza Farruxovna (American Journals, 2023)
The research of paremiological units denoting time in English is the focus of the current essay. First, it needs to be stressed how significant a role time plays in our lives. It is a proverbs article. The abundance of paremiological time units in the English language reflects our appreciation of time's critical role in our daily lives. These proverbs, which have been passed down through the years and are ingrained in our society, give us means to consider and articulate our connection with time. These proverbs serve as a helpful reminder that time is a valuable resource that we must manage carefully if we are to have happy and meaningful lives, whether we are talking to friends, conducting business, or thinking back on our lives.
Keywords: paremiological units, proverbs, time flies, time heals all wounds, time is money, timing is everything, time is a great teacher, in the nick of time, time and tide wait for no man.